2014
DOI: 10.1016/j.mhpa.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Associations of overall sitting time and sitting time in different contexts with depression, anxiety, and stress symptoms

Abstract: Spending a lot of time sitting has been linked to more depressive symptoms and spending a lot of time engaged in screen-based sitting has been linked to greater likelihood of having mental disorders and poorer psychological distress. The purpose of this study was to examine whether overall sitting time and time spent sitting in different contexts was associated with depression, anxiety, or stress symptoms. Sitting time (time spent sitting on typical work-and non-work days while engaged in leisure activities, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(111 citation statements)
references
References 49 publications
1
109
1
Order By: Relevance
“…TA B L E 2 Stress, anxiety, and depression per participants' demographic characteristics (N = 244) 17 On the other hand, one study showed that while sedentary behavior was significantly related with anxiety and depression, no significant correlation was found with stress. 39 In addition, another study reported no correlation between sedentary behavior and mental health, 15 contradicting the results of this study. Additionally, participants with more than 6 h of seated working were found to have a significantly higher level of psychological distress compared to those who had less.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…TA B L E 2 Stress, anxiety, and depression per participants' demographic characteristics (N = 244) 17 On the other hand, one study showed that while sedentary behavior was significantly related with anxiety and depression, no significant correlation was found with stress. 39 In addition, another study reported no correlation between sedentary behavior and mental health, 15 contradicting the results of this study. Additionally, participants with more than 6 h of seated working were found to have a significantly higher level of psychological distress compared to those who had less.…”
Section: Discussioncontrasting
confidence: 80%
“…Research on the correlation between university students’ sedentary behavior and mental health is limited; however, a 6‐year cohort study on university graduates in Spain revealed that participants who were seated for over 42 h per week were 1.3 times more likely to experience mental disorders such as stress, anxiety, and depression compared to participants who sat 10.5 h per week . On the other hand, one study showed that while sedentary behavior was significantly related with anxiety and depression, no significant correlation was found with stress . In addition, another study reported no correlation between sedentary behavior and mental health, contradicting the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents rate how often they feel a certain way (e.g., "These days, the people in my life would be better off if I were gone"), ranging from not at all true for me (1) to very true for me (7). Six items (7,8,10,13,14) have to be recoded before computing. Any report outcome higher than the 75th percentile score of 49 would be defined as unsatisfied with interpersonal needs (Cronbach's α: 0.855; range: 15-96).…”
Section: Interpersonal Needsmentioning
confidence: 99%
“…This should not be surprising, considering suicidal ideation and behavior are known as outcomes of feeling trapped in a stressful situation, with no evident escape or rescue possible 51 ; this has been found in diverse populations and in the context of various disorders and research methodologies [45][46] . Despite prevalence of poor psychosocial status among STI patients, huge gaps are still visible in concern and service, due to inadequate information and emotional support, and a shortage of qualified psychosocial professional treatment 8,[52][53][54] .…”
Section: Verification Of Syndemic Effect Of Psychosocial Variablesmentioning
confidence: 99%
See 1 more Smart Citation